2017
DOI: 10.1038/s41598-017-16922-0
|View full text |Cite|
|
Sign up to set email alerts
|

Altered resting-state brain activity in Parkinson’s disease patients with freezing of gait

Abstract: Freezing of gait (FOG) is a common and debilitating symptom in Parkinson’s disease (PD). The current study investigated alterations of resting-state spontaneous brain activity in PD patients with FOG. A total of 29 patients with FOG, 28 patients without FOG and 31 controls were included. All subjects underwent resting-state functional MRI, and the amplitude of low-frequency fluctuation (ALFF) was calculated to measure the spontaneous brain activity. Between-group differences and correlations with FOG severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 65 publications
6
35
0
Order By: Relevance
“…These findings suggest disease-related alterations of functional activities that provide physicians sufficient information to get involved with early diagnosis and treatment. Our findings are also coherent with the alternative functional features in cortical regions, brainstem, and limbic regions discovered in previous studies [ 32 , 33 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…These findings suggest disease-related alterations of functional activities that provide physicians sufficient information to get involved with early diagnosis and treatment. Our findings are also coherent with the alternative functional features in cortical regions, brainstem, and limbic regions discovered in previous studies [ 32 , 33 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…As an important relay hub within the motor circuit, specific neurons of the ventrolateral and reticular nucleus in the thalamus are modulated during locomotion and can transmit integrated signals to the motor cortex (Marlinski, Nilaweera, et al, 2012;. Moreover, impaired thalamic activity was found to be related to the freezing of gait in Parkinson disease (Mi et al, 2017). With regard to gait performance, a number of structural and functional imaging studies have demonstrated thalamic involvement in this specific motor function.…”
Section: Discussionmentioning
confidence: 99%
“…For example, functional activation in the thalamus was observed during a walking task in healthy subjects but not in individuals with gait disorders, and the degree of thalamic activation was negatively correlated with gait performance scores (Iseki et al, 2010). Moreover, impaired thalamic activity was found to be related to the freezing of gait in Parkinson disease (Mi et al, 2017). Structurally, thalamic atrophy can partially account for the compromised walking speed in multiple sclerosis patients (Motl, Zivadinov, Bergsland, & Benedict, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The middle frontal gyrus is mainly involved in higher cognitive functions, especially executive functions (John et al, 2006). Furthermore, a functional MRI (fMRI) study using amplitude of low-frequency fluctuation (ALFF) also found abnormal ALFF in the frontal, parietal, and temporal areas and cerebellum in PD-FOG, and found a significant correlation between ALFF changes in the middle frontal gyrus and FOG severity (Mi et al, 2017). This finding suggested that executive function impairment in the frontal regions was involved in PD-FOG.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with PD-FOG are observed to have impaired regions mainly concentrated in the frontal area and the cerebellum (Jha et al, 2015;Mi et al, 2017). Therefore, it is hypothesized that the brain functional impairments, particularly in the frontal executive and cerebellar networks, may be involved in the pathophysiology of PD-FOG.…”
Section: Introductionmentioning
confidence: 99%